Post-fire recovery of arthropod assemblage in an area of Brazilian savanna - Cunha, Hélida Ferreira da; Ramalho, Werther Pereira; Dias, Amanda Martins; Peixoto, Brenda Romeiro; Jesus, Gabriel Sampaio; Oliveira, Jennifer de Paula; Silva, Thamara Missel Pereira da (EntomoBrasilis, 2020)
Fire is a frequent agent of disturbance in tropical savannas (e.g., Brazilian Cerrado), but relatively few studies have analyzed how the arthropod community responds to fire disturbance. Following the incursion of an accidental fire into a Cerrado fragment in Central Brazil, we investigated whether the arthropod community is structured by abiotic (climate or fire) or biotic (succession) factors. Our study commenced one week after fire and during the six months afterward. We found 22 arthropod orders, of which Diptera, Hymenoptera, Hemiptera, Blattaria and Coleoptera were the most representative. More than 40% of the arthropod abundance was recorded 40 days after the fire event. The overall arthropod abundance and richness fluctuated in the six months following the fire and does not seem to be related to climatic variables. Temporal beta diversity was explained by a reduction in richness differences along the intervals of time, but the community recovery needs to be treated with caution. The increase in replacement in the last intervals in relation to the fire event indicates that biotic interactions may occur with the arrival of late colonizers and suggest that arthropod communities need a long time to be restructured. These results indicate that the processes of restructuring of the arthropod communities after human-induced fire events are temporally complex, involving loss, gain and taxon replacement, but long-term studies are still needed to understand the dynamics of communities.